2002
DOI: 10.1021/ar0100125
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Nature Catalysis:  Developing C−C Bond Formations Catalyzed by Late Transition Metals in Air and Water

Abstract: This Account outlines the recent efforts of developing catalysis under the ambient conditions of air and water for synthetic purposes from the author's laboratory. The discussions are focused on catalytic reactions (mostly C-C bond formations) other than oxidations via late transition metals. It includes the following aspects: (1) copper-catalyzed C-C bond formations; (2) palladiumcatalyzed C-C bond formations; (3) rhodium-catalyzed C-C bond formations; (4) ruthenium-catalyzed olefin isomerizations and C-H act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…(28)]. [81,82] Later, Li and co-workers found that silver complexes, such as Cy 3 PAgCl, were also a choice of catalyst for the addition of terminal alkynes to aldehydes. [83] Interestingly, the phosphine ligand served as a remarkable chemo-switch for the reaction of aldehydes with alkynes in the presence of amines in water.…”
Section: 3 Reaction With Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…(28)]. [81,82] Later, Li and co-workers found that silver complexes, such as Cy 3 PAgCl, were also a choice of catalyst for the addition of terminal alkynes to aldehydes. [83] Interestingly, the phosphine ligand served as a remarkable chemo-switch for the reaction of aldehydes with alkynes in the presence of amines in water.…”
Section: 3 Reaction With Carbonyl Compoundsmentioning
confidence: 99%
“…(82)]. The water soluble catalyst was reused for 8 times without any significant loss in catalytic activity.…”
Section: Enyne Cyclizationmentioning
confidence: 99%
“…In many cases, because of hydrophobic effects, using water as a solvent not only accelerates reaction rates but also enhances reaction selectivities, even when the reactants are sparingly soluble or insoluble in the medium. Furthermore, the low solubility of oxygen gas in water, an important property in the early development of life in an anaerobic environment, can facilitate airsensitive transition-metal catalysis in open air (61). The use of water as a solvent also implies the elimination of tedious protection-deprotection processes for certain acidic-hydrogen-containing functional groups, which contributes to the overall synthetic efficiency.…”
Section: Solventsmentioning
confidence: 99%
“…[33][34][35][36][37] Especially, the development of more efficient and sustainable catalysts that are effective in only water has been desired. [38][39][40][41][42] However, the achievement of high reaction efficiency with metal catalysts in water is not easy. To overcome the poor solubility of organic compounds and deleterious effects for metal catalysts in water, ingenious aids such as microwave heating, organic co-solvents, and surfactants are often necessary.…”
Section: Palladium-catalyzed 12-addition Of Organoboronic Acids To Amentioning
confidence: 99%
“…To overcome the poor solubility of organic compounds and deleterious effects for metal catalysts in water, ingenious aids such as microwave heating, organic co-solvents, and surfactants are often necessary. [33][34][35][36][37][38][39][40][41][42] Despite these efforts, reported examples of transition metalcatalyzed arylation of aldehydes with organoboron reagents in only water are quite scarce and have unresolved issues in reaction systems and substrate generality. 43,44) The performance of palladium/thioether-imidazolinium chloride system was examined in the phenylation of 2-naphthaldehyde 7b using water as solvent (Table 4).…”
Section: Palladium-catalyzed 12-addition Of Organoboronic Acids To Amentioning
confidence: 99%